2018
DOI: 10.1093/jac/dky310
|View full text |Cite
|
Sign up to set email alerts
|

Dosing vancomycin in the super obese: less is more

Abstract: Empirical vancomycin dosing informed by common clinical variables, including standardized creatinine, with subsequent individualization using AUC-targeted TDM can optimize therapy in obese and super obese adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 17 publications
1
40
0
Order By: Relevance
“…Our results on vancomycin clearance and volume of distribution in obese individuals puts forward what was known on vancomycin PK in obesity. Regarding clearance, predominantly retrospective studies also found a larger vancomycin clearance in obese compared to nonobese individuals . One prospective rich sampling PK study in healthy obese individuals, similar to our study design but with only 6 obese individuals included, found a linear relationship of TBW with vancomycin clearance, in contrast to the power relationship as found in our study .…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…Our results on vancomycin clearance and volume of distribution in obese individuals puts forward what was known on vancomycin PK in obesity. Regarding clearance, predominantly retrospective studies also found a larger vancomycin clearance in obese compared to nonobese individuals . One prospective rich sampling PK study in healthy obese individuals, similar to our study design but with only 6 obese individuals included, found a linear relationship of TBW with vancomycin clearance, in contrast to the power relationship as found in our study .…”
Section: Discussionsupporting
confidence: 67%
“…This might be explained by the relatively low body weight in the obese group (mean TBW 94.3 kg). Other reports in which obese patients were included, show conflicting results on the best predictive covariate for vancomycin clearance, varying from CG with TBW, serum creatinine, or a combination of serum creatinine, age, TBW and sex . These results might be explained by differences in studied body weights or employed sampling schedules (i.e.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations